Effects Of Core Stability Training On Shooting Success And Jump In Young Basketball Player –(a Field Study For The U13 Basketball Team) - Harieche , Imene (sports creativity, 2025)
This research aims to identify the degree of involvement of core stability on the jump and the improvement of shooting success in young basketball players (u13) . Methods: 30 players from the basketball team (U.S.C) Union Sportive Constantine. Who were divided into two experimental and control groups: age: 13.06 ± 0.85 years, height: 162.13 ± 6.51cm, weight: 57.26 ± 7.97kg),Two weeks were devoted to the tests (pre-tests), and (post-tests) .The investigations concerned the evaluation of the (vertical jump and horizontal jump) for the physical tests; and the shooting tests (1-2 ) to assess the success of the shots, and the ten-week period was devoted to the proposed program. The results: the proposed program had a significant impact on the horizontal jump of young players, since, and at the level of the success of the shots (P < 0.05) for the experimental group. The proposed program seems to greatly influence the performance of the players, which is particularly well transferred to the level of the effectiveness of the shots Keywords: Core Stability -shooting success -jump- basketball.